Modification of the Automatic Control System for Arduino ATmega 328P-Based Water Gallon Cleaner - Kharisma Ramadhan; Lutfi Hinda Mukti; M. Raghib Alashbahanni Mahfudz; Muhammad Dafa Dezan Rezaputra; M. Taufiqul Hafizh (Bulletin of Computer Science and Electrical Engineering, 2021)
Humans are living things that have 60 trillion cells to build the body, each cell of the human body contains 70% more water. Humans need water that is suitable for consumption. Water that is fit for consumption is water that has been processed or without processing that has met the requirements and can be drunk immediately. Various factors can cause water quality to decline, one of which is a water container in the form of gallons of water. From the results of a survey of students, 69.2% of students stated that drinking water on campus was not adequate. Meanwhile, 16.9% stated that it was not suitable and 13.8% of the other students stated that drinking water was suitable for consumption. So that the control system is modified on the existing devices so that they can work more effectively and efficiently. Furthermore, the research data was taken using quantitative data analysis techniques with descriptive statistics and the calculation of the average relative error. In the resulting data, the relative error value of the working time variable is 0.51% and 17.2% of the variable delay. And the relative variable error value is 18.3%. For the level of particle content in water in gallon 1 an average of 54 mg / L with an average temperature of 27.44 ° C and in gallon 2 of 52.6 mg / L with an average temperature of 28 ° C.